A comprehensive review of integrating biostimulants and biopesticides for organic berry farming: exploring challenges and opportunities for Africa - Mounaimi, Sana; Hamim, Ahlam; El Boukhari, Mohammed El Mehdi; Elarroussi, Hicham; Lyamlouli, Karim (Frontiers in Sustainable Food Systems, 2024)
Agriculture plays a pivotal role in Africa, contributing significantly to sustainable farming practices and the establishment of resilient food systems. Within this context, the use of various types of biostimulants, including microbial biostimulants such as Plant Growth-Promoting microorganisms (PGPM) and non-microbial products like Algal extract, humic acid, and protein hydrolysates, as well as biopesticides, emerges as a promising strategy to bolster sustainable agriculture, particularly in the realm of organic berry production. These substances have the potential to enhance crop growth, fortify stress tolerance, and optimize nutrient absorption, benefiting both human health and the environment. This paper aims to explore the opportunities and challenges associated with incorporating plant biostimulants into organic berry production within the African agricultural sector. To achieve this objective, an extensive and comprehensive review encompassing scientific literature, policy documents, and global data was conducted. The primary focus of this review was to investigate the current state of biostimulant adoption in organic berry farming within the African agricultural sector, with a specific emphasis on identifying potential opportunities and discussing the benefits derived from their application. Additionally, we addressed the challenges encountered and proposed practical approaches to achieving sustainable agriculture. The findings and conclusions of our review reveal the transformative potential of biostimulants in organic berry production. The evidence points to remarkable advancements in plant growth, plant health, overall yield, and fruit nutritional quality. By implementing these substances, we can also minimize the ecological footprint of agricultural practices. However, several challenges remain, including limited accessibility, insufficient awareness and knowledge regarding biostimulant usage, and a shortage of research specific to African agriculture. To overcome these challenges and achieve sustainable agriculture, this paper recommends practical approaches such as raising awareness, investing in research and development, and promoting the use of biostimulants through policy interventions and capacity-building programs. We underscore the importance of stakeholder participation and local adaptations for effectively integrating biostimulants in African agriculture. The significance of integrating plant biostimulants in organic berry production lies in advancing sustainable agriculture. This paper aims to explore the opportunities and challenges associated with incorporating plant biostimulants into organic berry production within Africa.